Langerhans cell histiocytosis: Diagnosis and Management - Lusiana; Hikari Ambara Sjakti; Githa Rahmayunita; Tjut Nurul Alam Jacoeb; Inge Ade Krisanti (Universitas Indonesia, 2019)
Langerhans cell histiocytosis (LCH) is a rare disorder characterized by abnormal clonal proliferation of Langerhans dendritic cells. The incidence of LCH is 1 to 3 cases per 1 million children worldwide, and occurs most frequently in children of 1-4 years of age. The etiopathogenesis of LCH, whether it is neoplastic or reactive, is still controversial. Langerhans cell histiocytosis has a wide spectrum of clinical features, and dermatological abnormalities usually occur early. The most frequent lesions are elevated yellowish-red translucent papules about 1-2 mm in diameter and generally located in seborrheic areas. The most recent classification (the Histiocyte Society study 2017) categorized LCH into four groups; a single system with involvement of unifocal or multifocal organs, lung LCH, and multi-system LCH with either low- or high-risk multiorgan involvement. The definitive diagnosis of LCH are typical morphology along with Birbeck granules and/or positive results on CD1a antigen stain on cells found on lesions. Treatment of LCH is multimodal, determined based on age, extent of lesion, organ involvement, and organ location.